Strengthening Science and Biology Teachers' Professional Competence Through Milk Processing Training as a Biotechnology Learning Resource - Yuni Pantiwati; Erna Retno Rahadjeng; Lud Waluyo; Tasya Novian Indah Sari; Sri Winarsih (Carmin: Journal of Community Service, 2026)
Malang Regency is known as the largest producer of dairy cow milk in East Java. This potential not only impacts the economic sector but can also be leveraged in education. Teachers need to possess professional competencies to optimize this potential as a learning resource. The objective of this community service project is to provide guidance on the production of dairy products as a learning resource for biotechnology, with the aim of enhancing teachers’ professional competencies in applying deep learning through the utilization of Malang Regency’s potential. The community service activities were conducted from October 2025 to April 2026. The partners for these activities were 10 science teachers and 10 biology teachers who are members of the Malang Regency Teachers’ Working Group. The community service activities included presenting instructional materials, hands-on practice in producing dairy products using conventional biotechnology, and analyzing the potential of these products as learning resources. Data collection to evaluate the success of the community service activities utilized a non-test method (self-assessment). The instrument used was a valid and reliable self-assessment form. The results of the community service program showed an increase in teachers’ professional competencies after participating in the activities, with an N-gain score of 0.56 (moderate category) for science teachers and 0.62 (moderate category) for biology teachers. In addition, participants successfully produced biotechnology-based dairy products (yogurt and butter) and conducted an analysis of the potential for utilizing dairy cow milk as a learning resource for biotechnology.